Feasibility study and kinetics of biohydrogen production by Escherichia coli from hydrolyzed sago wastewater - Mohamad Puad, Noor Illi; Saipullah, Nur Syafiqah Yasmin; Ulhiza, Tami Asti (Penerbit Akademi Baru, 2018)
The demand of hydrogen gas (H2) has increased considerably in recent years since it is a clean energy source and used as feedstock for some industries. However, H2 is most commonly produced from non-renewable sources that is considered as a less ecofriendly process. To avoid any environmental issues, another alternative is to produce this renewable H2 biologically. In this study, sago wastewater (SWW) was utilized as a substrate for Escherichia coli (E. coli) as the H2-producing bacteria. The main aim is to compare the performance of E. coli in producing biohydrogen (bioH2) from acid-hydrolyzed SWW and pure glucose in terms of total cell number, glucose concentration and bioH2 production. Based on the results, E. coli was able to produce bioH2 from SWW with about 30% less than pure glucose for its cumulative bioH2 production. Several kinetic parameters for bioH2 production by E. coli using SWW were determined from Monod model which are Yxs (1.7128 g/g), Yps (0.175 mol/mol), Ypx (0.0001 g/g),μ 1/0.345 h and td (2.01 h). In addition, a cumulative H2 production curve fitted by the modified Gompertz equation suggested that Hmax, Rmax and λ from this study were 1 mL, 0.05 mL/h, 1.003 h, espectively. The findings from this study concluded the potential of using hydrolyzed SWW in producing bioH2.